ARTIFICIAL INTELLIGENCE – THE RISK OF MISUSE AND THE PATH TO CRIME - Mohamed Djemaa; Kheireddine Ziane (International Journal of Innovative Technologies in Social Science, 2025)
This study examines the transformations that societies have undergone as a result of technological advancement, with a particular focus on artificial intelligence as one of the most prominent aspects of this progress. It clarifies the concept of artificial intelligence and its historical development, and highlights its benefits in various fields such as education, medicine, and industry, thanks to its ability to learn and adapt rapidly. However, the study also draws attention to its increasing dangers, especially when misused, as it can be exploited in committing cybercrimes such as forgery, fraud, and media falsification. The study emphasizes the need for strict legislation to limit these risks, particularly given its potential impact on the job market and on social and economic balances.